Model Konseling TERUS: Intergrasi Nilai Tepo Seliro dan Rukun Agawe Santosa dalam Menghadapi Keberagaman Sosial-Keagamaan - Kurniawati, Anisa Yulia; Rusdiana, Fendi Krisna (Jurusan Bimbingan dan Konseling Islam, 2025)
Socio-religious diversity in Indonesia is both a richness and a challenge which, if not properly managed, may trigger conflicts and divisions. East Java, as a multicultural region, possesses local wisdom in the form of the values Tepo Seliro (empathy and tolerance) and the motto Rukun Agawe Santosa (harmony brings prosperity), both of which are relevant for strengthening social harmony. This study aims to propose a counseling model based on East Javanese local wisdom in addressing diversity, employing a literature review method on multicultural counseling and Javanese culture. The findings indicate that the integration of these two values gives rise to the TERUS Counseling Model (Tepo Seliro & Rukun Agawe Santosa), which emphasizes four stages: cultivating empathy, self-reflection, fostering harmony, and achieving collective well-being. This model offers advantages such as simplicity, cultural relevance, and alignment with universal Islamic values. However, it also has limitations, particularly in its applicability beyond the Javanese cultural context, and requires specific training for counselors to internalize these values effectively. Therefore, the TERUS Model is deemed a feasible multicultural counseling approach that can strengthen tolerance, prevent conflict, and build a peaceful and inclusive society. This study contributes to multicultural counseling literature by proposing a culturally grounded counseling model that integrates Javanese local wisdom into a structured conceptual framework.